First-line therapy with daratumumab, lenalidomide and dexamethasone for patient with POEMS syndrome: A case report - E. Amabile; F. Fazio; M. Martelli; MT. Petrucci (Leukemia Research Reports)
POEMS syndrome (polyneuropathy, organomegaly, endocrinopathy, M–protein, skin changes syndrome) is a rare condition due to an underlying plasma cell neoplasm whose clinical presentation can be various so it could lead to delayed diagnosis and treatment. The pathogenesis of the syndrome is not well understood, and its therapy is adapted from other plasma cell disorders with the aim of alleviating symptoms, decreasing end-organ damage, improving quality of life and prolonging overall survival. We report a case of a 71 years-old woman who has been treated with continuous DRd (daratumumab, lenalidomide and dexamethasone) scheme.